2023
DOI: 10.1007/s11121-022-01470-5
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Elder Maltreatment: an Opportunity for Prevention Science

Abstract: Elder maltreatment (EM) has been understood as a worldwide major public health threat for decades, yet it remains a form of victimization receiving limited attention, resources, and research. EM, which includes caregiver neglect and self-neglect, has far-reaching and long-lasting impacts on older adults, their families, and communities. Rigorous prevention and intervention research has significantly lagged in proportion to the magnitude of this problem. With rapidly growing population aging, the coming decade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…By 2030, one in six people worldwide will be aged 60 or older, and approximately 16% will experience at least one form of maltreatment. 25 A recent review aiming to describe the status of EA prevention research on a global scale identified 72 articles published in the last 6 years. Several gaps were identified by the authors in the EA literature including the need for sensitive and valid tools to identify EA.…”
Section: Discussionmentioning
confidence: 99%
“…By 2030, one in six people worldwide will be aged 60 or older, and approximately 16% will experience at least one form of maltreatment. 25 A recent review aiming to describe the status of EA prevention research on a global scale identified 72 articles published in the last 6 years. Several gaps were identified by the authors in the EA literature including the need for sensitive and valid tools to identify EA.…”
Section: Discussionmentioning
confidence: 99%
“…From a preventive standpoint, communities can create structures to meet the specific needs that guarantee the right to age with dignity and security, that is, to be part of a greater social project in which everyone should be included, including older people. On the other hand, there is an emerging need to raise awareness and re-educate societies regarding elder abuse [ 52 ]. To this end, we suggest the creation of specific training actions and preventive social programs in schools and public and private institutions, to deconstruct prevailing ageist stereotypes still culturally present in today’s society.…”
Section: Discussionmentioning
confidence: 99%
“…The ever-increasing number of senior citizens (age >60 years) across the globe and the advent of newer and better diagnostic tools for immune-mediated diseases has produced an increase in the incidence of inflammatory diseases. While the general population grew from one billion in the year 1800 to eight billion at present, and it is estimated that by 2030 one in six people in world will be aged sixty or older (Bolkan et al, 2023; Pereira et al, 2023). In addition to this, studies suggest that there is an increased risk of developing immunemediated diseases to the individuals who got SARS-CoV-2 infections (Kim et al, 2024).…”
mentioning
confidence: 99%